State of the art in development of molecularly imprinted biosensors. Issue 3 (12th July 2021) - Wu, Licheng; Li, Xiaolei; Miao, Haohan; Xu, Jingjing; Pan, Guoqing
Abstract: Biosensors are a class of smart devices fabricated for target analyte detection. A biosensor is commonly made of three basic components: a specific bioreceptor, a physicochemical transducer, and a signal processing device. The bioreceptor part features one of the more crucial technologies of a biosensor to perform specific detection of analytes. They commonly make use of various molecular recognition elements, such as enzymes, natural receptors, antibodies, nucleic acid aptamers, and even synthetic receptors. Then, the molecular recognition events of these bioreceptors can be translated into readable signals in various forms like electrochemical, optical, piezo/pyro electric, etc. Finally, these signals are mathematically processed for quantitative analysis. Nowadays, the great advances in biomimetic materials, in particular the synthetic receptors based on molecularly imprinted polymers (MIPs), promote tremendous development of biosensors. Integration of this field with artificial intelligence enables emerging design of advanced biosensors, which has moved from concept to implementation, meanwhile facing new opportunities and challenges. With no doubt, bioreceptor innovation based on molecular imprinting is an emerging driving force for biosensors development. In this review paper, we provide an overview of MIP‐based biosensors, and also their challenges and opportunities moving forward toward wearable devices are discussed. Abstract : Molecularly imprinted polymers (MIPs) are the most promising antibody‐like artificial materials, which have been widely used in biosensor development as antibody alternatives. This review paper presents the recent progress of MIP‐based biosensors, and comprehensively discusses the challenges and opportunities of biosensors moving forward toward real applications.